2020
DOI: 10.1111/petr.13832
|View full text |Cite
|
Sign up to set email alerts
|

Early school‐age cognitive performance post–pediatric heart transplantation

Abstract: Background: As survival in pediatric heart transplantation (HTx) has improved due to medical advances, the analysis of long-term outcomes impacting quality of life such as cognition and development becomes increasingly important. Neuropsychological assessments provide a comprehensive understanding of individual needs, allowing for the development of tailored recommendations and interventions. Methods: Routine neuropsychological assessment was completed between 5 and 7 years of age in this cohort of pediatric H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
3
7
0
Order By: Relevance
“…At the same time, patients were most impaired on the numerical operations subtest, with the group average significantly below the standard mean of 100, producing a large effect size. This parallels the findings of a recent study, showing that children who underwent heart transplant were impaired on the three WIAT subtests used here, with numerical operations producing the lowest group mean (Gold et al, 2020). While numerical operations are not often studied in developmental populations with history of HI, our study still replicates findings from some studies where difficulties with numerical operations were found (Isaacs et al, 2001;Taylor et al, 2011).…”
Section: Impairment In Attainment and Its Neural Correlatessupporting
confidence: 89%
“…At the same time, patients were most impaired on the numerical operations subtest, with the group average significantly below the standard mean of 100, producing a large effect size. This parallels the findings of a recent study, showing that children who underwent heart transplant were impaired on the three WIAT subtests used here, with numerical operations producing the lowest group mean (Gold et al, 2020). While numerical operations are not often studied in developmental populations with history of HI, our study still replicates findings from some studies where difficulties with numerical operations were found (Isaacs et al, 2001;Taylor et al, 2011).…”
Section: Impairment In Attainment and Its Neural Correlatessupporting
confidence: 89%
“…At present, more and more studies use the WPPSI-IV for clinical intervention and neuropsychological evaluation. For example, patients with post-paediatric heart transplantation (Gold et al, 2020), premature children (Ahn et al, 2019), patients treated with propranolol for infantile haemangioma treatment (González-Llorente et al, 2017), patients with anaemia (Murtaza et al, 2019), and so on had their cognitive performance evaluated by the WPPSI-IV test. Few studies has been reported that evaluated cognitive performance of children with severe HFMD (Chang et al, 2004), those that did were also limited to EV-A71 infection.…”
Section: Introductionmentioning
confidence: 99%
“…However, childhood represents a vulnerable developmental period. Research has identified a high prevalence of trauma within the pediatric transplant field, 47,48 as well as a high prevalence of neuropsychological issues among pediatric SOT patients when compared to population norms 49–51 . While such findings might point to considerable risk factors of transplantation on long‐term QoL, they might also be capturing deleterious impacts of the underlying disease, which may further justify the benefits of early transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Research has identified a high prevalence of trauma within the pediatric transplant field, 47,48 as well as a high prevalence of neuropsychological issues among pediatric SOT patients when compared to population norms. [49][50][51] While such findings might point to considerable risk factors of transplantation on long-term QoL, they might also be capturing deleterious impacts of the underlying disease, which may further justify the benefits of early transplantation. Moreover, it is important to note that the rate of organ re-transplantation in adult patients, who are often transplanted in childhood, is high, 52 which may partially explain findings of older age at assessment and longer time since transplant to be associated with poorer overall QoL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation